Parents' attitudes and behaviours towards recommended vaccinations in Sicily, Italy - Giammanco Giuseppe; Privitera Donatella; Platania Marco; Coniglio Maria; Pignato Sarina (BMC, 2011)
Abstract Background Since a long time, Italy has maintained a dual system to administer childhood immunisations, that is a certain number of mandatory vaccinations and a number of recommended vaccinations. The study aimed to explore the issues surrounding parental acceptance or non-acceptance of the recommended vaccinations for children. Methods Parents of children aged 3-5 years of day-care centres in Sicily were asked to fill out an anonymous questionnaire. Determinants of the attitude towards recommended vaccinations and social influence on the decision-making process were assessed using logistic regression analysis. Results Of the 1,500 selected parents, 81.0% participated in the study. Prior to the survey, the majority of children (97.6%) received recommended vaccines. Most parents (74.4%) received information about vaccinations from Family Paediatricians, showed a good knowledge about the side effects of the vaccines (73.1%), did not worry about their potential dangerousness (53.0%) and would have accepted their children to be vaccinated even if it was not required for day care (84.1%). The majority (79.9%) were not disposed to follow the advises of the anti-vaccination movements. Parents' background characteristics, sources of information and social influence were not significantly associated with parental acceptance of recommended vaccines for childhood. Conclusions This study suggests that health information by Family Paediatricians is significantly associated with parental acceptance of recommended vaccinations.